Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Eight Years of Multiparty Democracy in Mozambique: The Public’s View - João Pereira; Ines Raimundo; Annie Chikwanha; Alda Saute; Robert Mattes (Afrobarometer Working Papers, 2003)
Since its emergence from a brutal, 17-year civil war, Mozambique’s process of political reform has faced a number of challenges. The first has been to empower ordinary Mozambicans by allowing them to participate in a democratic system and enabling them to voice their demands to the state and hold it accountable. The second has been to rebuild a state with the capacity to respond to citizen demands effectively. And given the long history of violent division, a third challenge has been to build a state that enjoys broad legitimacy – a legitimacy that spans the bitter partisan divides of the past, enabling the formation of a strong, authoritative state with the ability to enforce the rule of law, but also the discipline to rule through transparent procedures. Perhaps the best evidence by which to judge the success of the process of political reform are the opinions of ordinary Mozambicans. Rather than looking to expert judgments or to measures of formal constitutional rights, we believe that the views of ordinary citizens – as the ultimate consumers of what democratic governments supply – can offer perhaps the most conclusive assessment of the quality of governance. What do they say? Through its partner in Mozambique, the Public Opinion Service of the Centre for Population Studies at the University of Eduardo Mondlane, the Afrobarometer surveyed a nationally representative sample of 1425 Mozambicans citizens, aged 18 years and older, using a multi-stage, area-stratified, clustered sample designed by the National Institute for Statistics. The survey was carried out between August and October 2002 in all 10 provinces of the Republic of Mozambique. At a confidence level of 95 percent, a sample of this size allows a confidence interval, or margin of error, of plus or minus 2.5 percent. This means that, had we interviewed every Mozambican, 19 times out of 20 the results would differ from those of this survey by no more than 2.5 percent. The evidence from this survey suggests that although Mozambique is plagued by what appear to be insurmountable problems, in general the country appears to be on the right path as an emerging democracy. While the society faces vast challenges of building human and social capital to empower citizens further and increase the capacity of the state, the democratization that has occurred since Mozambique opened its political space has gone a long way in propelling democracy forward.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; accountability / responsabilização; civil society / sociedade civil